PENGARUH LABEL HALAL DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK INDOMIE (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Julia Lestari; M Hufron; M Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe purpose of this study are: 1) To determine the influence of halal and price tags simultaneously to the purchase decision. 2) To determine the influence of halal and price tags partially on purchasing decisions. The type of sampling used is accidental sampling, the sample in the study amounted to 96 Students Faculty of Economics and Business Islamic University Of Malang. The results of research by using multiple linear regression analysis shows that the variable of halal label and price simultaneously have an influence on to purchase decision variable, likewise halal label variable and price partially have an influence on purchasing decision variable.  Keywords: Halal label, price, purchase decision